Identification of a new intronic BMPR2-mutation and early diagnosis of heritable pulmonary arterial hypertension in a large family with mean clinical follow-up of 12 years. - Katrin Hinderhofer; Christine Fischer; Nicole Pfarr; Justyna Szamalek-Hoegel; Mona Lichtblau; Christian Nagel; Benjamin Egenlauf; Nicola Ehlken; Ekkehard Grünig (PLoS ONE, 2014)
Mutations in the bone morphogenetic protein receptor 2 (BMPR2) gene can lead to hereditary pulmonary arterial hypertension (HPAH) and are detected in more than 80% of cases with familial aggregation of the disease. Factors determining disease penetrance are largely unknown.A mean clinical follow-up of 12 years was accomplished in 46 family members including echocardiography, stress-Dopplerechocardiography and genetic analysis of TGF-β pathway genes. Right heart catheterization and RNA-analysis was performed in members with pathological findings.Manifest HPAH was diagnosed in 8 members, 4 were already deceased, two died during the follow-up, two are still alive. Normal pulmonary artery systolic pressure at rest but hypertensive response to exercise has been identified in 19 family members. Analysis of BMPR2 transcripts revealed aberrant splicing due to an insertion of an intronic Alu element adjacent to exon 6. All HPAH patients and 12 further asymptomatic family members carried this insertion. During follow-up two family members carrying hypertensive response and the Alu insertion developed manifest HPAH.This is the first report of an intronic BMPR2 mutation due to an Alu element insertion causing HPAH in a large family which has been confirmed on RNA-level. Only those members that carried both hypertensive response and the mutation developed manifest HPAH during follow-up. Our findings highlight the importance of including further methods such as RNA analysis into the molecular genetic diagnostic of PAH patients. They suggest that at least in some families hypertensive response may be an additional risk factor for disease manifestation and penetrance.